Performance of electron reconstruction and selection with the CMS detector in proton-proton collisions at root s=8 TeV - (:unkn) unknown (IOP PUBLISHING LTD, 2015)
The performance and strategies used in electron reconstruction and selection at CMS are presented based on data corresponding to an integrated luminosity of 19.7 fb(-1), collected in proton-proton collisions at root s = 8TeV at the CERN LHC. The paper focuses on prompt isolated electrons with transverse momenta ranging from about 5 to a few 100 GeV. A detailed description is given of the algorithms used to cluster energy in the electromagnetic calorimeter and to reconstruct electron trajectories in the tracker. The electron momentum is estimated by combining the energy measurement in the calorimeter with the momentum measurement in the tracker. Benchmark selection criteria are presented, and their performances assessed using Z, SIC, and J/psi decays into e(+)+e(-) pairs. The spectra of the observables relevant to electron reconstruction and selection as well as their global efficiencies are well reproduced by Monte Carlo simulations. The momentum scale is calibrated with an uncertainty smaller than 0.3%. The momentum resolution for electrons produced in Z boson decays ranges from 1.7 to 4.5%, depending on electron pseudorapidity and energy loss through bremsstrahlung in the detector material.
Keywords: Pattern recognition; cluster finding; calibration and fitting methods; Performance of High Energy Physics Detectors